O professor de português língua estrangeira no contexto universitário inglês: estudo de caso - Oliveira, Alexandrina (2015)
This thesis addresses, amongst other issues, the phenomenon of the professional development and teacher training of the University Portuguese language teachers in England. Nowadays society needs a new profile of teacher who is capable of facing various challenges. These are essentially related to technologies and new knowledge, according to the European Higher Education Area. Therefore, the focus of our study is directed to the training of the University Portuguese Language Teachers at the English universities, in particular at the University of Nottingham (developing a case study) in order to contribute for a reflection of their needs of training and preparation for their job. We also seek for the students’ opinion on this subject and we try to understand the context of a society clearly dominated by a culture of monolonguism and resistence to the learning of foreign languages. For this reason, and because the number of investigations on the subject is scarce, this is a contribution to reflect on the main aspects to take into consideration in the preparation of training for this specific professionals.